Pengaruh Penggunaan Kahoot sebagai Media Pembelajaran Interaktif untuk Meningkatkan Minat Belajar Siswa Kelas VI pada Mata Pelajaran PKN SD YPK Bethania Mariadei - Anni Maria; Lirhan Lirhan; Selviana Vindirani Mamori; Desy Putri Sahara; Andi Nurhartina; Marlin Katulung (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
Research. Elementary School Teacher Education Study Program, STKIP PGRI Papua. The purpose of this study is to examine the Influence of Using Kahoot as an Interactive Learning Media to Increase the Learning Interest of Sixth-Grade Students in Civic Education at SD YPK Bethania Mariadei. This type of research is Experimental research. The population in this study consists of students at SD Bethania Mariadei, while the research sample is 21 students in the sixth grade. Data collection was conducted through questionnaires and documentation. The collected data was analyzed using descriptive statistics and inferential statistics techniques. Based on the hypothesis testing results, the calculated t-value is 2.926 with a significance of 0.009. The significance value shows 0.009 < 0.05, so H0 is rejected and H1 is accepted, which leads to the conclusion that there is a significant and positive effect of using Kahoot media as an interactive learning tool to increase the learning interest of sixth-grade students in Civics subjects at SD YPK Bethania Mariadei. The Kahoot Interactive Learning Media can be applied for Civics learning in elementary schools. Keywords: Kahoot, Learning Media, Learning Interest, Civics.